Antibiotics for treating scrub typhus - Panpanich R. (2014)
Scrub typhus is a bacterial disease in regions of Asia and the Pacific. Antibiotics (chloramphenicol, tetracycline, and doxycycline) have been used to treat the disease. Resistance to these antibiotics has been reported.